Effect of Giving of Ethanol extract of Ginger (Zingiber officinale Rosc.), Pandan leaves (Pandanus amarylifolius Roxb), Citronella (Cymbopogon nardus (L.) Randle), Cinnamon (Cinnamomum burmanii B.) on Cholesterol Reduction in Male Strain Rats (Rattus Norvegicus) - ElySabet Pratiwi Siagian; Rumondang Fransiska Tampubolon; Ida Duma Riris (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Cholesterol in the blood is a form of sterol derived from a lipid molecule that serves as the main structural component of plasma membrane. Atherosclerosis is a change characterized by thickening of the arterial walls due to the accumulation of cholesterol in the intima of blood vessels. By using SPSS analysis, it was found that the Shapiro-Wilk Normality Test with a sig value > 0.05, the data were normally distributed. The results of the analysis in the Test of Homogeneity of Variences table obtained a Sig Value 0.106. This the value of Sig = 0.106 > 0.05, them ho is accept. Thus the ethanol extract of ginger, pandan leaves, citronella, cinnamon, has the potential to reduce cholesterol levels. By using four different doses, the rat group at a dose 100mg/kgbw showed cholesterol levels of 90,75(mg/dl) ± 11,58, the rat group at a dose 200mg/kgbw showed cholesterol levels of 95,5(mg/dl) ± 6,80, the rat group at a dose 300mg/kgbw showed cholesterol levels of 75,75 (mg/dl)± 2,06, the rat group at a dose 400mg/kgbw showed cholesterol levels of 67,5mg/dl ± 2,64.